The Emerald handbook of digital media in Greece : journalism and political communication in times of crisis - Veneti, Anastasia; Karatzogianni, Athina (Digital activism and society., 2020)
The Emerald Handbook of Digital Media in Greece: Journalism and Political Communication in Times of Crisis addresses the impact of new technologies and the socio-economic crisis on journalism and presents the empirical applications of digital media in political communication and in a number of social settings including the environment, homelessness, migration and social movements. From 2008 Greek political communication and journalism were hit by two major forces. Firstly, the financial crisis, which progressed to an economic, then a political, and eventually a social and cultural crisis in Greece. Secondly, the disruptive transformation and acceleration of everyday networked technologies, which impacted news media in Greece throughout the same period. This book offers a comprehensive overview of the changing environment in Greece since the beginning of the global (and consequently local) financial crisis of 2008, and a contemporary discussion around the developments brought forward by digital media and communication technologies, specifically addressing political communication and journalism.